2013
DOI: 10.4103/0975-5950.117885
|View full text |Cite
|
Sign up to set email alerts
|

Unilocular radiolucencies of anterior mandible in young patients: A 10 year retrospective study

Abstract: Introduction:Mandibular anterior region is an uncommon site for occurrence of intrabony pathologies. Unilocular presentation of a lesion is again less common than multilocular appearance. Demographically, most lesions occur in middle to elderly age group. The study is designed to review the pathologies manifesting a combination of these rare demographic and radiological criteria.Materials and Methods:A retrospective analysis of patients with anterior unilocular radiolucencies of mandible in young patients was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Even though the majority of the reported cases showed predilection to mandibular posterior region [2,4], the present case showed anterior mandiblular predilection which is an unusual location of Keratocystic odontogenic tumor.This was in accordance with other studies which described odontogenic keratocystic lesion in the anterior mandibular segment [7,8].…”
Section: Discussionsupporting
confidence: 93%
“…Even though the majority of the reported cases showed predilection to mandibular posterior region [2,4], the present case showed anterior mandiblular predilection which is an unusual location of Keratocystic odontogenic tumor.This was in accordance with other studies which described odontogenic keratocystic lesion in the anterior mandibular segment [7,8].…”
Section: Discussionsupporting
confidence: 93%
“…The #MeSH words used were adenomatoid odontogenic tumor, odontogenic, and case report. We reviewed the data associated with AOT from 2000 to 2014,[3456781314151617181920212223242526272829303132333435363738394041424344454647484950515253545556575859606162636465666768697071727374757677787980818283848586878889919293] and it was found that in the last 14 years, there was a record of 255 reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…The #MeSH words used were adenomatoid odontogenic tumor, odontogenic, and case report. We reviewed the data associated with AOT from 2000 to 2014,[ 3 4 5 6 7 8 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 ...…”
Section: Discussionmentioning
confidence: 99%